1996
DOI: 10.1080/0263514960140108
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Environment of High School Students in Chemistry and Biology Laboratories

Abstract: In this article a comparison of students' perceptions of laboratory classes in chemistry and biology is presented. By using the Science Laboratory Environment Inventory (SLEI), pronounced and significant differences between chemistry and biology laboratory environments were found on two of the subscales: 'Integration' that describes the extent to which its laboratory activities are integrated with non-laboratory and classroom learning and 'Open-endedness', a subscale that measures the extent to which the labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 20 publications
1
24
0
2
Order By: Relevance
“…The percentage of lessons that show some degree of openness to inquiry (levels 2a, 2b and 3) increases from earth science (one of 12 lessons, 8%), chemistry (13%), biology (17%) to physics (21%). These findings are consistent with those of Hofstein et al (1996) who found that Israeli students rated biology laboratory classes to be more open ended than laboratory classes in chemistry. It may be that physics offers more opportunities for investigation style laboratory work than the other disciplines.…”
Section: Differences Between Groupssupporting
confidence: 94%
See 1 more Smart Citation
“…The percentage of lessons that show some degree of openness to inquiry (levels 2a, 2b and 3) increases from earth science (one of 12 lessons, 8%), chemistry (13%), biology (17%) to physics (21%). These findings are consistent with those of Hofstein et al (1996) who found that Israeli students rated biology laboratory classes to be more open ended than laboratory classes in chemistry. It may be that physics offers more opportunities for investigation style laboratory work than the other disciplines.…”
Section: Differences Between Groupssupporting
confidence: 94%
“…Responding to the SLEI, upper secondary students from six different countries rated their science laboratory classes as having very low levels of open-endedness. Also using the SLEI, Holstein, Cohen and Lazarowitz (1996) found that Israeli students rated biology laboratory classes to be more open ended than laboratory classes in chemistry.…”
mentioning
confidence: 99%
“…In addition, Hofstein et al (1996) found significant differences between students’ perceptions of their actual chemistry and biology laboratory environments, specifically for the dimensions of integration, open-endedness, rule clarity, and organization (Hofstein et al 1996). In that study, the biology and chemistry laboratory environments differed in the extent to which they engaged students in group work and investigation as well as more open-ended problem-solving and discussion.…”
Section: Introductionmentioning
confidence: 99%
“…The Student Learning Environment Inventory (SLEI) [9] was employed in order to examine students' perceptions of a learning environment which integrates the automation devices in basic chemical experiments.…”
Section: Introductionmentioning
confidence: 99%